Sediment echosounder raw data (Atlas Parasound P70 echosounder entire dataset) of RV POLARSTERN during cruise PS123 - Yvonne Schulze Tenberge; Simon Dreutter; Andrea Catalina Gebhardt (PANGAEA, 2025)
Sediment echosounder (Teledyne Parasound P70 echosounder) data are generally retrieved to get information on the characteristics of the upper tens of meters of the sub-seafloor. Raw primary high frequency (PHF) and secondary low frequency (SLF) echo sounding data were retrieved during POLARSTERN cruise PS123 and are archived here in ASD and PS3 format. The entire dataset of cruise PS123 is archived here.